Pengembangan Pendidikan Karakter di Sekolah untuk Membentuk Generasi Muda yang Unggul - Adilla Aisyahrani (Educazione: Jurnal Multidisiplin, 2024)
Character education is an important aspect in forming a superior young generation. Schools as an educational institution have a strategic role in instilling character values in students. This article aims to discuss the development of character education in schools to form a superior young generation. The method used in this research is a qualitative research method with a case study approach and examining various sources such as scientific journals, books and articles related to character education. The research results show that developing character education in schools can be done through various approaches. The development of character education in schools must be carried out on an ongoing basis and involve all related parties, including teachers, parents and the community. With joint efforts, it is hoped that a young generation of excellence and noble character can be created who is ready to build the nation and state.